Abnormal pontine activation in pathological laughing as shown by functional magnetic resonance imaging. Issue 12 (16th November 2006) - Kosaka, H; Omata, N; Omori, M; Shimoyama, T; Murata, T; Kashikura, K; Takahashi, T; Murayama, J; Yonekura, Y; Wada, Y
Abstract : To explore the aetiology of pathological laughing, a 65-year-old woman with pathological laughing was examined by 3-T functional magnetic resonance imaging (fMRI) before and after treatment with drugs. Here, we report that the patient consistently showed exaggerated pontine activation during the performance of three tasks before treatment, whereas abnormal pontine activation was no longer found after successful treatment with the selective serotonin reuptake inhibitor, paroxetine. Our findings in this first fMRI study of pathological laughing suggest that serotonergic replacement decreases the aberrant activity in a circuit that involves the pons.